40 Hadiths on core values SASMEC @IIUM (40 Hadis berkenaan nilai murni SASMEC @IIUM) - Che Ahmad, Aminudin; Al Azmi, Abdul Rahman; Nawi, Roswati; Wan Halimi, Wan Syafiq Asyraf; Rohaizad, Muhammad Zulfadzly; Mohamed, Nor Faridah; Zoll, Mohd Afiq; Abdul Aziz, Nor Fatihah Atikah; Md Yusoff, Md Hanin (2021)
This book of 40 hadiths on the respective SASMEC @IIUM core values act s as a reference for SASMEC @IIUM staff to read and refer for a better understanding of selected core values